Improving the Diagnosis and Treatment of Chronic Endometritis in Women of Reproductive Age (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Chronic endometritis is one of the most common inflammatory diseases of the female reproductive system. Timely treatment of the disease is insurance against serious complications, including oncology and infertility. After fertilization (or transfer during IVF procedure), the embryo is attached to the lining of the uterus. But the mucous membrane damaged by inflammation may not accept the attempts of the embryo. The main reason for the development of endometritis, as mentioned above, is inflammatory diseases.If an inflammatory process develops in the vagina, often caused by sexually transmitted infections, these microorganisms enter the uterine cavity, then the fallopian tubes and the abdominal cavity, causing the inflammatory process. can cause.Inflammation is a universal protective response of the body. Its results are the activation of the immune system aimed at suppressing and destroying the microbe. However, in the tissues, often after inflammation, a dense connective tissue is formed, which leads to a violation of the blood supply to the tissues.One of the most unpleasant moments is that the inflammatory process can go from an acute stage to a chronic - "dormant" state. And it can worsen due to unfavorable environmental factors or general health, with the development of immunodeficiency conditions, including during the IVF program or pregnancy.